Characterization of Argentinean commercial bee pollen intended for human consumption - Fernández, Leticia Andrea (2023)
Bee pollen is consumed as a dietary supplement. Its quality parameters are regulated by the Argentine Food Code (AFCode). The present study characterized 10 commercial dehydrated samples from five Argentine provinces to provide information on hygienic quality and health safety. We assessed their microbiological quality, including potential mycotoxins. We also determined their botanical origin and moisture. Results showed that seven out of ten samples presented lower counts of culturable heterotrophic mesophilic bacteria than those allowed by the AFCode. In contrast, all samples showed higher filamentous fungi and yeast counts than the level approved by the AFCode. No fumonisin or deoxynivalenol was detected; we observed only aflatoxin B2 in one sample and ochratoxin A in two. The results of the botanical origin of samples showed that all samples had a predominant pollen type, except one. The microbiological quality of all samples agreed with that required by the AFCode, except filamentous fungi and yeasts. In addition, we found variations among samples from the same province. Therefore, if pollen is intended for human consumption, appropriate hygiene standards must be applied to all bee pollen production operations.